Uma construção geométrica dos números reais - Santos, Simone de Carvalho (2015)
This study aims to present a geometric construction of real numbers characterizing them as numbers that express a measure. In this construction, each point in an oriented line represents the measure of a segment (a real number). Based on ve axioms of Euclidean geometry it was de ned an order relation, a method to add and multiply points so that it was possible to demonstrate that the line has a full ordered body of algebraic structure that we call the set of real numbers. To do so, it were presented historical elements that allow us to understand the emergence of irrational numbers as a solution to the insu ciency of rational numbers with respect to the measuring problem, the evolution of the concept of number, as well as the importance that the strict construction of real numbers had to the Foundations of Mathematics. We display a construction of rational numbers from the integernumbers as motivation for construction of numerical sets. Using the notion of measure,we show a geometric interpretation of rational numbers linking them to the points of an oriented line to demonstrate that they leave holes in the line and conclude on the need to build a set that contains the rational numbers and that ll all the points of a line. The theme is of utmost importance to the teaching of mathematics because one of the major goal of basic education is to promote understanding of numbers and operations, to develop number sense and to develop uency in the calculation. To achieve this, it is necessary to assimilate the r